Correlation of JAK2V617F mutational status in primary myelofibrosis with clinico-hematologic characteristics and international prognostic scoring system scoring: A single center experience - Neha Singh; Sudha Sazawal; Ashish Upadhyay; Sunita Chhikara; Manoranjan Mahapatra; Renu Saxena (Wolters Kluwer Medknow Publications, 2015)
Introduction: Somatic mutation in the exon 14 of Janus Kinase 2 gene is an established diagnostic marker in bcr-abl negative myeloproliferative neoplasms, especially primary idiopathic myelofibrosis (PIMF). Aim: Our primary aim was to find out the correlation between the JAK2V617F mutational status and the clinico-hematologic characteristics, as well as the international prognostic scoring system (IPSS) scoring of patients with PIMF. Materials and Methods: Clinical and hematologic features were reviewed for 68 patients with primary idiopathic myelofibrosis (PIMF). JAK2V617F mutation status was analyzed by amplification refractory mutation screening-polymerase chain reaction. The patients were further stratified into low, intermediate-1, intermediate-2 and high-risk groups on the basis of IPSS scoring. Results: The JAK2V617F mutation was detected in 58.8% patients. Univariate analysis of variables at presentation identified that JAK2V617F negative patients were significantly associated with more severe anemia (P = 0.045), younger age (P = 0.008), higher transfusion requirement (P = 0.017), and thrombocytopenia (P = 0.015). Patients who were homozygous for JAK2V617F mutation were associated with thrombocytosis (P = 0.014) and also had higher median total leucocyte count (P = 0.20) than the other groups. No significant correlation was detected between JAK2V617F mutational status and the presence of constitutional symptoms, spleen size, grade of bone marrow fibrosis or prognostic risk stratification of the PIMF patients. Conclusion: The variations in the prognostic implication of PIMF patients with mutation status as stated by various publications worldwide, reinstates the need for larger prospective studies using standardized JAK2V617F quantification methods as well as estimation of other newer molecular markers to develop deeper insight into various molecular alterations involving PIMF patients in India as well as worldwide.